Harvey Sarcoma Virus: A Second Murine Type C Sarcoma Virus with Rat Genetic Information - Scolnick, Edward M. (1974)
The nucleic acid sequences found in the Harvey strain of murine sarcoma virus have been analyzed by RNA·[(3)H]DNA and [(3)H]RNA·DNA hybridization techniques. The Harvey strain of murine sarcoma virus has been found to possess at least two sets of nucleic acid sequences. One set of sequences is contained in the Moloney strain of mouse type-C virus, and the other set is contained in DNA transcripts synthesized in endogenous reactions containing rat type-C virus(es). The nucleic acid sequences that are detected in the Harvey sarcoma virus with the DNA probes synthesized from the rat type-C virus(es) are related to the rat sequences detected in the Kirsten strain of murine sarcoma virus. The results support the model that both Kirsten and Harvey sarcoma viruses arose through a process of recombination or reassortment between mouse type-C viruses and sequences in rat cells and suggest that the information for transformation of fibroblasts may be contained in the rat type-C or cellular genome.